In vitro quality of amotosalen‐UVA pathogen‐inactivated mini‐pool plasma prepared from whole blood stored overnight. Issue 7 (6th August 2018) - Ravanat, Catherine; Dupuis, Arnaud; Marpaux, Nadine; Naegelen, Christian; Mourey, Guillaume; Isola, Herve; Laforêt, Michel; Morel, Pascal; Gachet, Christian
Abstract : Background and objectives: Small batch‐pooled (mini‐pool) whole blood (WB)‐derived plasma could be an alternative cost‐effective source of therapeutic plasma (TP), but carries an increased risk of transfusion‐transmitted infection due to exposure of the recipient to several donors. This risk can be mitigated by inactivation of pathogens susceptible to the amotosalen‐UVA (AUVA)‐treatment. We evaluated the conservation of coagulation factors in AUVA‐plasma prepared from WB stored overnight under routine operating conditions, to determine its therapeutic efficacy. Thrombin generation (TG) by the AUVA‐plasma was used to provide an integrated measure of the hemostatic capacity. Materials and methods: WB‐donations (~450 ml) stored overnight were processed to prepare five leucocyte‐depleted plasma mini‐pools (1300 ml), which were divided into two parts and treated with AUVA. Each mini‐pool yielded six AUVA‐plasma units (200 ml) which were frozen (−25°C) within 19 h of WB‐collection. Their hemostatic quality was evaluated before and after treatment for up to 12 months of storage. Results: Immediately after AUVA‐treatment, the regulatory criteria for FVIII activity and fibrinogen content were met. As compared to untreated plasma there was a reduction in fibrinogen (14%), FV (9%), FVII (25%) and FVIII (32%). However, TG was similar in treated and untreated plasma at all‐time‐points. Conclusions: Frozen WB‐derived AUVA‐plasma prepared from mini‐pools within 19 h of WB‐collection met the quality standards required for TP and retained hemostatic capacity for up to 12 months. This product could provide a cost‐effective convenient substitute for apheresis plasma.